1987
DOI: 10.1037/0882-7974.2.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Metamemory in older adults: The role of monitoring in serial recall.

Abstract: Older and younger adults were asked to think aloud while studying sets of pictures matched in difficulty for immediate serial recall. When instructed only to remember, young adults tended to study longer, rehearse more, and recall better than did older adults on the most difficult lists. Young adults were also much more likely to spontaneously test themselves during study in the most difficult condition. Older adult groups instructed either to study longer or to self-test, both showed improved recall. Only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 19 publications
4
52
0
Order By: Relevance
“…To address the concern about processing strategy, studies exploring metacognition and aging (e.g., Brigham, & Pressley, 1988;Murphy, Schmitt, Caruso, & Sanders, 1987) have indicated that older adults may be less efficient than younger adults in adopting processing strategies to solve cognitive tasks and that, once adopted, these strategies may not be used as efficiently compared to younger adults. However, if task-relevant strategies can be effectively adopted and utilized by older adults, these strategies can improve performance as well as generalize to tasks with similar elements.…”
Section: Resultsmentioning
confidence: 98%
“…To address the concern about processing strategy, studies exploring metacognition and aging (e.g., Brigham, & Pressley, 1988;Murphy, Schmitt, Caruso, & Sanders, 1987) have indicated that older adults may be less efficient than younger adults in adopting processing strategies to solve cognitive tasks and that, once adopted, these strategies may not be used as efficiently compared to younger adults. However, if task-relevant strategies can be effectively adopted and utilized by older adults, these strategies can improve performance as well as generalize to tasks with similar elements.…”
Section: Resultsmentioning
confidence: 98%
“…For example, Dustman et al (1984; see also Hawkins, Kramer, & Capaldi, 1992) found improvements in the performance of a number of tasks following the participation in a short-term program of aerobic exercise by a group of previously sedentary old adults. Similarly, training programs have been found to dramatically improve the performance of elderly adults on a variety of cognitive skills such as visual search (Ball, Beard, Roenker, Miller, & Griggs, 1988), fluid intelligence (Baltes, Sowarka, & Kliegel, 1989), memory (Murphy, Schmitt, Caruso, & Sanders, 1987;Verhaeghen, Marcoen, & Goossens, 1992), and dual-task processing (Baron & Mattila, 1989;Larish, Kramer, DeAntonna, & Strayer, 1993). Thus, this research suggests that it may be feasible to improve the inhibitory functions of the elderly through training.…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches have been used, including surveys to obtain students' selfreported use of testing (Carrier, 2003;Gurung, 2005;Hartwig & Dunlosky, 2012;Karpicke, Butler, & Roediger, 2009;Kornell & Bjork, 2007;Kornell & Son, 2009;McCabe, 2011;Wissman et al, 2012) and laboratory observation studies that examine how students spontaneously use testing (Bottiroli, Dunlosky, Guerini, Cavallini, & Hertzog, 2010;Karpicke, 2009;Kornell & Bjork, 2008;Kornell & Son, 2009;Murphy, Sanders, Gabriesheski, & Schmitt, 1981;Murphy, Schmitt, Caruso, & Sanders, 1987;Son, 2005). The present study uses the latter approach, but evidence from both is relevant.…”
Section: Prior Literature On Self-regulated Use Of Testing and Feedbackmentioning
confidence: 94%